The Effects of Money Beliefs on Investment Addiction - Ali Bahrami; Amirhossein Taebi Noghondari; Hadis Zeinali (Iranian Journal of Accounting, Auditing & Finance)
As the impact of culture, especially money belief, is greater than the rational analysis of the capital market in developing countries, the expansion of Iran’s capital market has led to an increased investment addiction. Since a few studies have been conducted in this area so far, this study investigates the impact of money beliefs on investment addiction. Thus, 415 questionnaires were distributed among investors, of which 346 were accepted. The data were analyzed using structural equations in AMOS software using the maximum likelihood estimation (MLE) method. The findings suggest that money worship and money status beliefs significantly affect investment addiction, whereas money avoidance belief does not affect investment addiction. In addition, the money vigilance belief has a significant negative impact on investment addiction. Given the effects of most money beliefs on investment addiction, policymakers and consultants of the capital market can readily safeguard traders from capital market dilemmas through effective money belief-building training.